Hubungan antara Pengetahuan, Sikap, dan Kenyamanan terhadap Kedisiplinan Pemakaian Masker pada Pedagang sebagai Upaya Pencegahan Penularan Covid-19 - Nugroho, Rizal Adi; Widowati, Evi (Center for Public Health Nutrition Studies, Universitas Negeri Semarang, Indonesia, 2023)
Background: Covid-19 is a respiratory tract infection. One way to prevent the spread of Covid-19 is through the use of masks. Important factors that influence the discipline of wearing masks are knowledge, attitudes and comfort. Market is prone to being one of the clusters for the spread of Covid-19 because market is a meeting point for many people, with various positions and conditions. Bukateja Market is an example of a market for implementing health protocols. After a mass rapid test was carried out on May 28, 2020 to all traders, there were 2 people who were declared reactive for Covid-19. From the initial observation study to 10 traders, 3 people (30%) did not wear masks. The purpose of this study is to find the relationship between knowledge, attitude and comfort towards the discipline of wearing masks at traders as an effort to prevent the transmission of Covid-19 (Case study at Bukateja Market). Methods: This type of research in this study is quantitative research, with an analytical survey method and the design of this study is cross sectional. The research sample used incidental sampling with a sample of 84 traders in Bukateja Market. Data was collected using questionnaire instruments and observation sheets. Results: The results of the study, there was no relationship between health knowledge and the discipline of wearing masks, there was a relationship between the attitude of wearing masks and the discipline of wearing masks, there was a relationship between the comfort of wearing masks and the discipline of wearing masks. Conclusion: Suggestions are to carry out systematic and massive supervision, provide supporting facilities, check hygiene standards, and provide education on the importance of wearing masks.